Rancang Bangun Aplikasi Monitoring Konsumsi Energi Listrik 1 Fasa Pelanggan Pln Pascabayar Berbasis Web Server - Irawan, Muhamad Angga; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Electricity is one of the sources of energy which is a major need in daily life. Appropriate efforts are needed so that the availability of electrical energy used can be maintained availability. Concern for each consumer in this case a large-scale 1-phase PLN customer, will have a broad impact if they make joint savings through a measurable mechanism for the use of electrical energy. Until now, PLN single-phase customers do not yet have facilities to get real-time information on household electrical energy usage. Thus designed an application that can measure, process data, and display the use of electrical energy which is named "AMoEL (Electric Energy Monitoring Application)". AMoEL can measure Current, Voltage, Power, Electric Energy and Rates. In testing the instrument, getting the results of varying measurement accuracy, where the instrument testing sample for 4 days obtained the value of the accuracy of energy (kWH), namely: the first day at 87.13%, the second day at 77.81%, the third day at 77.46 %, and fourth day is 85.25%. Any data that has been successfully sent will be stored and displayed on the webserver, so customers can access information on home electricity usage easily.Keywords: Current Sensor, Voltage Sensor, Cosphi Sensor, Php Website, MySQL Database.